2016
DOI: 10.1140/epjc/s10052-016-4235-1
|View full text |Cite
|
Sign up to set email alerts
|

Phase transition of charged Black Holes in Brans–Dicke theory through geometrical thermodynamics

Abstract: In this paper, we take into account black hole solutions of Brans-Dicke-Maxwell theory and investigate their stability and phase transition points. We apply the concept of geometry in thermodynamics to obtain phase transition points and compare its results with those, calculated in the canonical ensemble through heat capacity. We show that these black holes enjoy second order phase transitions. We also show that there is a lower bound for the horizon radius of physical charged black holes in Brans-Dicke theory… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 47 publications
(32 citation statements)
references
References 80 publications
1
31
0
Order By: Relevance
“…The second one is considered by Mirza and Mansoori (MM) in [32][33][34][35], which is based on conjugate thermodynamic potentials, specifically chosen to reflect the relevant thermodynamic properties of system under consideration. Some applications of these approaches to different gravitational systems can be found for example in [32][33][34][35][36][37][38][39][40][41][42][43][44][45][46]. In order to identify the admissible thermodynamic metrics for a given black hole solution, a case by case study is required.…”
Section: Introductionmentioning
confidence: 99%
“…The second one is considered by Mirza and Mansoori (MM) in [32][33][34][35], which is based on conjugate thermodynamic potentials, specifically chosen to reflect the relevant thermodynamic properties of system under consideration. Some applications of these approaches to different gravitational systems can be found for example in [32][33][34][35][36][37][38][39][40][41][42][43][44][45][46]. In order to identify the admissible thermodynamic metrics for a given black hole solution, a case by case study is required.…”
Section: Introductionmentioning
confidence: 99%
“…BD (Brans-Dicke) theory has been significant in the explanation of the cosmic inflation [46], and consistent with Dirac's large number hypothesis and Mach's principle [47,48]. Thermodynamics of charged black holes in Brans-Dicke theory have been studied in [49][50][51][52]. This theory produces the solar system experimental observations with a specific domain of BD parameter ω [53].…”
Section: Introductionmentioning
confidence: 86%
“…Recent studies in the context of the GTs approaches for the black hole thermodynamics have shown that the Ricci scalars of Weinhold, Ruppeiner and Quevedo metrics may lead to extra divergencies which are not matched with the bound points and the phase transitions [97][98][99][100]. In other words, there were cases of mismatch between divergencies of the Ricci scalar and the mentioned points (bound and phase transition points), and also existence of extra divergency unrelated to these points were reported [97][98][99][100]. In order to overcome the shortcomings of the mentioned methods (Weinhold, Ruppeiner and Quevedo metrics), the HPEM method was introduced and it was shown that the specific structure of this metric provides satisfactory results regarding GTs of different classes of the black holes.…”
Section: Geometrical Thermodynamicsmentioning
confidence: 99%
“…[97][98][99][100], for more details). In other words, obtained results of these three approaches were not consistent with those extracted from other methods.…”
Section: Introductionmentioning
confidence: 99%